2014
DOI: 10.1371/journal.pone.0104745
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin Attenuates Aβ1–42-Induced Neuroinflammation and Inhibits NF-κB Pathway

Abstract: Neuroinflammation induced by beta-amyloid (Aβ) plays a critical role in the pathogenesis of Alzheimer’s disease (AD), and inhibiting Aβ-induced neuroinflammation serves as a potential strategy for the treatment of AD. Oridonin (Ori), a compound of Rabdosia rubescens, has been shown to exert anti-inflammatory effects. In this study, we demonstrated that Ori inhibited glial activation and decreased the release of inflammatory cytokines in the hippocampus of Aβ1–42-induced AD mice. In addition, Ori inhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 35 publications
(37 reference statements)
1
65
0
1
Order By: Relevance
“…Notably, a study from Zhong et al (2009) indicates that chronic intraperitoneal injection of PF significantly attenuates memory impairment and reduces neuronal apoptosis in Aβ 1-42 -treated rats in vivo (Zhong et al, 2009), implying PF may act beneficially in the treatment of AD. Over-activated NF-κB signaling leading to pathogenic inflammation has been reported to exacerbate the cytotoxic effects of Aβ oligomers in brain (Wang et al, 2014c). Interestingly, PF can abolish ischemia-induced abnormal activation NF-κB signaling in rat brain (Guo et al, 2012), but we lack of information of its effect on Aβ 1-42 -induced microglial NF-κB activation.…”
Section: Discussionmentioning
confidence: 90%
“…Notably, a study from Zhong et al (2009) indicates that chronic intraperitoneal injection of PF significantly attenuates memory impairment and reduces neuronal apoptosis in Aβ 1-42 -treated rats in vivo (Zhong et al, 2009), implying PF may act beneficially in the treatment of AD. Over-activated NF-κB signaling leading to pathogenic inflammation has been reported to exacerbate the cytotoxic effects of Aβ oligomers in brain (Wang et al, 2014c). Interestingly, PF can abolish ischemia-induced abnormal activation NF-κB signaling in rat brain (Guo et al, 2012), but we lack of information of its effect on Aβ 1-42 -induced microglial NF-κB activation.…”
Section: Discussionmentioning
confidence: 90%
“…The hope is to get satisfactory results from clinical studies with compounds that have been successful in vitro, ex vivo, and/or in vivo experiments, such as the administration of molecules like acetylpuerarin,138 edaravone,139 palmitoylethanolamide,38 N -[2-(4-hydroxyphenyl)ethyl]-2-(2,5-dimethoxyphenyl)-3-(3-methoxy-4-hydroxyphenyl) acrylamide (compound FLZ),140 oleuropeinaglycone,141 oridonin,142 protocatechuic acid,143 resveratrol,110 rutin,144 or immunotherapies145,146 and vaccinations 147…”
Section: Future Research Directionmentioning
confidence: 99%
“…Cheng et al demonstrated that oridonin induces L929 cell apoptosis by regulation of ROS-mediated signaling pathways, and simultaneously induces autophagy to block apoptosis by regulating p38/NF-κB signaling [39]. The anti-inflammatory and cytoprotective effects of oridonin have also been demonstrated using in vitro and in vivo models focused on the Nrf2 and NF-κB signaling pathways [4042]. …”
Section: The Natural Product Oridonin and Its Mechanisms Of Actionmentioning
confidence: 99%
“…Hence, additional attention should also be paid to explore other beneficial effects, including cytoprotection [40], anti-mycobacterial [126, 127], anti-fibrosis [128, 129] and anti-inflammatory effects [130], produced by oridonin and its derivatives. Interestingly, recent findings support that oridonin and its analogues may be considered a promising therapeutic option for Alzheimer’s disease (AD) and other neurodegenerative diseases [41, 42]. …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%